New opportunities and challenges in financing of the enterprises of small and average business in Russian Federation - T. A. Shpilkina (Путеводитель предпринимателя, 2020)
The mechanisms of financing of the enterprises of small and average business and their main features. The possibilities and problems of development of subjects of small and average business in the current economic conditions. The role of crowdfundingplatforms in the development of small businesses.